Mechanisms of Manganese Oxide Electrocatalysts Degradation during Oxygen Reduction and Oxygen Evolution Reactions - Speck, Florian; Santori, Pietro Giovanni; Jaouen, Frederic; Cherevko, Serhiy (Journal of Physical Chemistry C, 2019)
Anion exchange membrane fuel cells and electrolyzers offer a unique opportunity of using non-noble metal electrocatalysts for catalyzing the sluggish oxygen reduction and oxygen evolution reactions (ORR, OER). In recent years, various Mn-based oxides were identified as promising catalysts for both reactions. While electrocatalytic activity of such oxides is well addressed, their stability is still to be proven. Herein, we investigate the stability of four main manganese oxide allotropes by following their Mn dissolution rate in operando ORR and OER conditions. Using an electrochemical on line inductively coupled plasma mass spectrometer (on line ICP MS), we uncover unexpected instability of this class of catalysts, with different degradation mechanisms identified under OER and ORR conditions. The reason for their degradation is shown to be related to the production of hydrogen peroxide species on manganese oxides during ORR. Furthermore, we discuss how limits in thermodynamically stable windows of each Mn oxidation state leads to increased dissolution during applications with high potential perturbations, i.e. change in load, start/stop conditions and especially bifunctional application. Therefore we recommend clear guidelines for future development of platinum group metal free electrocatalysts for affordable alkaline energy conversion technologies.
CRIS-Team Scopus Importer:2019-10-22